THE HUMAN FACTOR AS A COMPARATIVE MARKETING ADVANTAGE OF THE REPUBLIC OF SERBIA IN THE NEW ECONOMIC AND GEOPOLITICAL CIRCUMSTANCES (Heritage, 2020)
Today in the new economic and geopolitical circumstances, in the era of globalization with which the world is affected, each individual country has the difficult task to allocate for something and on this basis quality economic and political positions. The Republic of Serbia, as well as any other small country, can and must offer only the best that it has.The people who are coming out as a product of an educational system, which for decades has graced these space are definitely the best of all what this country has always had. However, the situation in the Europe and in the international scene is constantly changing, many other countries our's competitors saw that to big countries may be in the field of interest only if they offer two things: either work or knowledge, or preferably both.Therefore, national education policy makers must continually take attention, except the needs of economic actors which are now present on the Serbian market, on the supply and demand in the domestic and international labor market. It takes ever greater speed and flexibility in creating new educational profiles that will monitor dynamic changes in the economic environment caused by information technology innovation and meet the needs of innovative companies for new human resources. Because,  in this way the Republic of Serbia will be interesting in the economically and politically sphare and through this work we want to show the importance of qualified human factor to create a comparative marketing advantages of the Republic of Serbia, in the Europe and in the world market too.
Keywords: human resources, the Republic of Serbia, the comparative marketing advantage, economic conditions, political circumstances